2011
DOI: 10.1007/s11430-011-4207-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of atmospheric boundary layer depth with thermodynamic processes at the land surface in arid regions of China

Abstract: The atmospheric boundary layer (ABL) is an important physical characteristic of the Earth's atmosphere. Compared with the typical ABL, the ABL in arid regions has distinct features and is formed by particular mechanisms. In this paper, the depth of the diurnal and nocturnal ABLs and their related thermodynamic features of land surface processes, including net radiation, the ground-air temperature difference and sensible heat flux, under typical summer and winter conditions are discussed on the basis of compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 9 publications
1
39
0
2
Order By: Relevance
“…By comparison with deserts and other arid regions that also have a high ABL [51][53], the elevation of the Tibetan Plateau makes it easy to demonstrate how transport processes in the UTLS over the plateau affect the ABL. A close surface-troposphere-stratospheric coupled system may exist over the plateau.…”
Section: Resultsmentioning
confidence: 99%
“…By comparison with deserts and other arid regions that also have a high ABL [51][53], the elevation of the Tibetan Plateau makes it easy to demonstrate how transport processes in the UTLS over the plateau affect the ABL. A close surface-troposphere-stratospheric coupled system may exist over the plateau.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies evaluated the accuracy of GTS1 observations [Tao et al, 2006;Bian et al, 2011] and indicated that the GTS1 radiosondes provide temperature profiles as accurate as the Vaisala RS80 profiles in the troposphere. The fine-resolution L-band radiosonde data have been used to study boundary layer features across China [Zhang et al, 2008;Yang et al, 2011;Zhang et al, 2011;Du et al, 2013;Guo et al, 2016].…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%
“…These studies have laid a solid foundation for a detailed understanding of the weather and climate in this region. In China, Zhang et al, , Zhang & Wang, utilized observations over Dunhuang to study the structure of the ABL and land surface processes. They found that the height of the ABL in Dunhuang can exceed 4,000 m in the summer when the sky is clear, which is actually the result of strong solar radiation and an extremely dry surface.…”
Section: Introductionmentioning
confidence: 99%